2014
DOI: 10.1097/tp.0b013e3182a860b8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Extracorporeal Membrane Oxygenation or Mechanical Ventilation as Bridge to Combined Heart-Lung Transplantation on Short-Term and Long-Term Survival

Abstract: HLT recipients bridged by MV or ECMO have increased short-term and long-term mortality. Further studies are needed to optimize survival in these high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…[1][2][3][4] It can be used for temporary support of critically ill patients. 2,[5][6][7] Although outcomes in patients supported by ECMO are poor, [8][9][10] they have improved in recent years. 11,12 As more and more patients are supported with these temporary devices, 13 many will go on to develop noncardiac surgical problems.…”
mentioning
confidence: 98%
“…[1][2][3][4] It can be used for temporary support of critically ill patients. 2,[5][6][7] Although outcomes in patients supported by ECMO are poor, [8][9][10] they have improved in recent years. 11,12 As more and more patients are supported with these temporary devices, 13 many will go on to develop noncardiac surgical problems.…”
mentioning
confidence: 98%
“…The survival benefits of ECMO use as a bridge for lung transplantation have long been debated. It has been reported that lung transplant recipients undergoing ECMO have increased short- and long-term mortality23, particularly those who receive a transplant after waiting for >14 days24. However, some recent reports showed that a combination of mechanical ventilation and ECMO is a viable bridging strategy, leading to acceptable patient outcomes25.…”
Section: Discussionmentioning
confidence: 99%
“…In HLT patients, recipients bridged by MV or ECMO have been shown to have increased short- term. Long-term mortality, and longer hospital stays [ 16 ]. However, in our study, we could not confirm significant difference of survival outcomes of the patients who required ECMO support (n=6) and MV (n=8) before HLT when compared to unsupported group.…”
Section: Discussionmentioning
confidence: 99%